EVOLUTION OF ARCHITECTURAL COMPOSITION PRINCIPLES IN SACRED ARCHITECTURE OF UKRAINE: FROM WOODEN CHURCHES TO MODERNIST INTERPRETATIONS - Дячок, Оксана; Колодрубська, Олександра; Вербовецький, Юрій; Білик, Мирослав; Миронюк, Софія (SWorldJournal, 2025)
This article analyzes the evolution of architectural composition in Ukrainian sacred buildings—from wooden tripartite churches of the 16th–18th centuries to contemporary modernist structures of the 20th–21st centuries. The relevance of the study is driven